Physiological and molecular analysis of salt tolerance in wheat (Triticum aestivum) recombinant inbred lines population (HD2851 × Kharchia 65) - ISMAIL, AHMED MOHAMMED; SINGH, PRADEEP KUMAR; KRISHNA, HARI; KUMAR, ARVIND; KULSHRESHTHA, NEERAJ; C, MAHENDRA; KUMAR, KANIKA (The Indian Journal of Agricultural Sciences, 2025)
Sodicity is a critical stress that significantly affects the yield and productivity of wheat. This stress can result in a range of physiological, biochemical, and molecular responses in plants, which can hinder their overall health and yield potential. Understanding these responses is key to developing salt-tolerant wheat (Triticum aestivum L.) varieties. The present study was carried out during 2022–23 and 2023–24 at ICAR-Central Soil Salinity Research Institute, Karnal, Haryana in which a population of 195 recombinant inbred lines (RILs) of wheat (HD2851 × KH65) was evaluated under control and sodicity conditions. Genotype HD2851 showed a more significant yield reduction (65.51%) under sodicity conditions compared to KH65 (45.08%). Following exposure to salt stress, the leaf tissues of KH65 exhibited 1.9-fold increase in Na+ content, while HD2851 showed 3.1-fold increase. Significant positive correlations (P˂0.01) were found between grain yield and several traits: chlorophyll content, K+/Na+ ratio, plant height, spike length, flag leaf area, and 1000-grain weight. Conversely, Na+ content exhibited a significant negative correlation (P˂0.01) with grain yield. The first two principal components accounted for 38.39% of the overall trait variation (PC1, 21.14%; PC2, 17.25%). In this study, the expression of TaNHX1, TaSOS1 and TaHKT2 genes was evaluated in the leaf tissues of salt-tolerant (KH65, RIL8 and RIL130) and salt-sensitive (HD2851, RIL61 and RIL154) wheat genotypes under salt treatment. The expression levels of TaNHX1, TaSOS1 and TaHKT2 genes were significantly higher in KH65, RIL8 and RIL130 genotypes following salt stress, suggesting enhanced capabilities for Na+ exclusion at the plasma membrane and Na+ sequestration in vacuoles. The information generated in the present study will be beneficial for improving salt tolerance in elite wheat genotypes.